Pengaruh Perencanaan Pajak dan Tunneling Incentive Terhadap Keputusan Transfer Pricing - Rossa, Elia; Ananta, Engela; Arbatona, Ian; Christian, Josua; Maharani, Kiran; Purba, Lidia Margaretta (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Multinational companies conducting transfer pricing research in Indonesia are typically manufacturers closely linked to subsidiaries or affiliates in other countries. The transfer pricing activities of international companies have a significant impact on a country's tax revenue, both directly and indirectly. This qualitative research, utilizing literature studies as the data collection method, delves into Tax Management literature, exploring components influencing transfer pricing decisions, including tax planning and tunneling incentives. The primary focus of this article is to formulate hypotheses on how tax planning and tunneling incentives can affect transfer pricing decisions. Literature review results indicate that tax planning significantly influences transfer pricing decisions, while tunneling incentives also wield substantial influence in this context.